2013
DOI: 10.1002/ejic.201201396
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Activation over TiIV: What Have We Learned from Studies on Ti‐Containing Polyoxometalates?

Abstract: Keywords: Polyoxometalates / Titanium / Hydrogen peroxide / Epoxidation / OxidationThis short review paper summarizes recent findings in the field of H 2 O 2 activation over Ti IV centers on the basis of model studies of Ti-containing polyoxometalates (Ti-POM) that used both experimental and computational techniques. Alkene epoxidation with H 2 O 2 mediated by two different POMs, the Ti-monosubstituted Keggin-type POM, [PTi(OH)-W 11 O 39 ] 4-(1), and the Ti-disubstituted sandwich-type POM, [Ti 2 (OH) 2 As 2 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 103 publications
(93 reference statements)
0
22
0
Order By: Relevance
“…We also evaluated the alternative mechanism B (Figure 2), which starts from the hydrolysis of compound 1 D yielding the monomeric forms [(γ‐SiTi 2 W 10 O 38 H 2 )(OH) 2 ] 4− ( 1 M ). In general, Group IV‐containing POMs have a strong tendency to form intercluster linkages and to interconvert between dimeric and monomeric species 10ad,g. 15 Moreover, the rate of thioether oxidation with H 2 O 2 catalysed by Ti‐substituted Keggin anions was related to the dissociation of the dimer to the monomer 10d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also evaluated the alternative mechanism B (Figure 2), which starts from the hydrolysis of compound 1 D yielding the monomeric forms [(γ‐SiTi 2 W 10 O 38 H 2 )(OH) 2 ] 4− ( 1 M ). In general, Group IV‐containing POMs have a strong tendency to form intercluster linkages and to interconvert between dimeric and monomeric species 10ad,g. 15 Moreover, the rate of thioether oxidation with H 2 O 2 catalysed by Ti‐substituted Keggin anions was related to the dissociation of the dimer to the monomer 10d.…”
Section: Resultsmentioning
confidence: 99%
“…Computational techniques have been successfully employed to get insight into the mechanisms of catalytic processes by POMs,11 including alkene epoxidation with H 2 O 2 catalysed by Ti‐substituted POMs 10b. 12 On the other hand, mechanistic studies (both experimental and theoretical) on POMs containing Ti dimers (small clusters) are scarce 10g. 13…”
Section: Introductionmentioning
confidence: 99%
“…In the case of vanadium, this was first systematically studied by Vandichel et al [104], whereas the case of titanium was tackled earlier by Sever and Root [111]. Some theoretical studies on titanium-catalyzed epoxidations also focused on this metal's ability to efficiently catalyze the epoxidation of olefins when immobilized into a heterogeneous matrix, such as silicates [112] or polyoxometalates [113,114]. These theoretical studies follow the same trend observed in the case of manganese-and iron-catalyzed epoxidations, with a predominance of DFT, with B3LYP as the preferred density function.…”
Section: Other Epoxidation Catalysts: a Brief Overviewmentioning
confidence: 99%
“…The difference in catalytic activity and product distribution between the two catalysts could be attributed to the different specific surface areas of these catalysts as seen in BET analysis where the specific surface area changes with Au content, and the chemical environment of the POM ions which could be altered after the deposition of Au species. Kholdeeva et al . suggested that the introduced species (Au) may act as the main active center for the activation of oxygen to form activated intermediates, which are suitable for the formation of oxidized products through a heterolytic oxidation mechanism.…”
Section: Resultsmentioning
confidence: 99%